2020 IEEE 21st International Conference on Computational Problems of Electrical Engineering (CPEE) 2020
DOI: 10.1109/cpee50798.2020.9238707
|View full text |Cite
|
Sign up to set email alerts
|

MCTS Based Agents for Multistage Single-Player Card Game

Abstract: The article presents the use of Monte Carlo Tree Search algorithms for the card game Lord of the Rings. The main challenge was the complexity of the game mechanics, in which each round consists of 5 decision stages and 2 random stages. To test various decision-making algorithms, a game simulator has been implemented. The research covered an agent based on expert rules, using flat Monte-Carlo search, as well as complete MCTS-UCB. Moreover different playout strategies has been compared. As a result of experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Comparing with our previous results [11], the use of expert rules has allowed to achieve a significant increase in the effectiveness of the method at a high level of difficulty. The extension of the algorithm is based on the limitation of analyzed actions.…”
Section: Mcts For the Lord Of The Ringssupporting
confidence: 45%
See 2 more Smart Citations
“…Comparing with our previous results [11], the use of expert rules has allowed to achieve a significant increase in the effectiveness of the method at a high level of difficulty. The extension of the algorithm is based on the limitation of analyzed actions.…”
Section: Mcts For the Lord Of The Ringssupporting
confidence: 45%
“…This allowed to perform a new analysis for games with high complexity level. We have demonstrated that the relative effectiveness of the mixed strategy proposed in [11] rises as the difficulty of the problem increases.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This allowed to perform a new analysis for games with high complexity level. We have demonstrated that the relative effectiveness of the mixed strategy proposed in [16] rises as the difficulty of the problem increases.…”
mentioning
confidence: 96%
“…Several precautions had been taken to reduce number of allowed moves. Using Action filtering and Obliged Actions are examples of successful domain-specific knowledge incorporation.This article is directly based on authors conference work [16]. The algorithm has been extended by adding more expert knowledge into the standard MCTS implementation.…”
mentioning
confidence: 99%